2011
DOI: 10.1111/j.1540-8167.2011.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Dofetilide Reduces the Frequency of Ventricular Arrhythmias and Implantable Cardioverter Defibrillator Therapies

Abstract: In patients with an ICD and ventricular arrhythmias, dofetilide decreases the frequency of VT/VF and ICD therapies even when other antiarrhythmic agents, including amiodarone, have previously been ineffective. Recurrences still occur in some patients requiring catheter ablation, mechanical support, or heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…A more recent study in 30 ICD recipients with drug-refractory VT/VF episodes showed a significant reduction in both monthly ventricular arrhythmia episodes (from 1.8 ± 4.5 to 1.0 ± 3.5, P  = 0.006) and monthly ICD therapies (from 0.9 ± 1.4 to 0.4 ± 1.7, P  = 0.037) after treatment with dofetilide. In addition, 83% of patients had complete suppression of VT/VF during their first month of treatment [60]. …”
Section: Discussionmentioning
confidence: 99%
“…A more recent study in 30 ICD recipients with drug-refractory VT/VF episodes showed a significant reduction in both monthly ventricular arrhythmia episodes (from 1.8 ± 4.5 to 1.0 ± 3.5, P  = 0.006) and monthly ICD therapies (from 0.9 ± 1.4 to 0.4 ± 1.7, P  = 0.037) after treatment with dofetilide. In addition, 83% of patients had complete suppression of VT/VF during their first month of treatment [60]. …”
Section: Discussionmentioning
confidence: 99%
“…58 Although dofetilide has only been studied in randomized controlled trials for atrial fibrillation, dofetilide may be an option for patients with VT, because there has been an association noted between dofetilide use and lower rates of VT and appropriate ICD therapy in patients with secondary prevention ICDs. 59 Ranolazine is a late sodium channel blocker that has been shown to decrease VT episodes within the first week after myocardial infarction, 60 and the ongoing (RAID) Ranolazine Implantable Cardioverter-Defibrillator Trial will answer the question about the benefit of ranolazine in preventing appropriate ATP, ICD shocks, or death in primary and secondary prevention ICD patients (NCT01215253). 61 When using antiarrhythmic medications in patients who have received ATP therapy, it is important to remember the effects of the antiarrhythmic medications on defibrillation thresholds.…”
Section: Medications For Treatment and Prevention Of Ventricular Tachmentioning
confidence: 99%
“…Another clinical trial documented a decrease in the frequency of defibrillation shocks in patients with an ICD and recurrent VT and VF receiving adjuvant therapy with dofetilide. Dofetilide decreases the frequency of VT/VF and ICD shocks even when other AADs including amiodarone have failed 55 .…”
Section: Role Of Antiarrhythmic Drugs In Patients With Icdsmentioning
confidence: 99%